Using Cooperative Learning (Team Pair Solo) to Improve Students Reading Comprehension - Wahyu Wibisono (Reforma : Jurnal Pendidikan dan Pembelajaran, 2017)
This research was aimed to apply cooperative learning (Team Pair Solo) as the technique to solve students problems in reading class of the third semester of nursing students in Stikes Patria Husada Blitar. This research design was a Classroom Action Research. The researcher used several instruments; such as observation checklist, field notes, and reading comprehension test. The finding showed that by using cooperative learning (Team Pair Solo), students comprehension in reading could be better than when they were taught by using traditional grammar translation method. This result could be seen from the data, in terms of the students individual reading comprehension test, in preliminary research, the number of students who passed the minimum passing grade (64) were only 2 students (20%). In Cycle 1, 10 students (100%) could pass the minimum passing grade (64). The improvement of students reading comprehension was due to the use of cooperative learning (Team Pair Solo) as the technique in teaching reading. It showed that by using cooperative learning (Team Pair Solo), students motivation and self-esteem increased since the cooperative learning (Team Pair Solo) could accommodate students to be well prepared to the reading passage by discussing in team, pair with other student, and finally they have great self-esteem to stand by their self in reading class. Consequently, students became more motivated in terms of in-class discussion and offered opinions since they were accustomed to express their idea through cooperative learning (Team Pair Solo).     It was suggested to all of English teachers/ lecturers to apply this technique as one of the methods to increase students motivation in English class and also could be used to increase students reading skill. Other researchers were expected to elaborate this cooperative learning with other technique so that there would be alot of technique could be used as refference in teaching english. It was suggested to all of English teachers/ lecturers to apply this technique as one of the methods to increase students motivation in English class and also could be used to increase students reading skill.Keywords: traditional grammar translation method, cooperative learning (Team Pair Solo), reading skill